Headache after pediatric traumatic brain injury: a comparison between a post-acute sample of children and adolescents and general population - Marina Zeldovich; Leonie Krol; Katrin Cunitz; Christian Auer; Daniel Pinggera; Victoria Schön; Philipp Geiger; Joachim Suss; Inga K. Koerte; Emilie Isager Howe; Nada Andelic; Anna Buchheim; et al. (The Journal of Headache and Pain)
Abstract Background Headache is one of the most common post-concussion symptoms following pediatric traumatic brain injury (TBI). To better understand its impact on young individuals, this study aims to investigate the prevalence of headache in a German-speaking post-acute pediatric TBI sample and compare it with the general population. In addition, factors associated with the development of pediatric post-TBI headache are investigated to improve the understanding of this condition. Methods A post-acute sample (3 months up to 10 years post-injury) comprising N = 463 children and adolescents aged 8 to 17 years from the TBI sample and N = 463 individuals from the general population matched for gender, age, and health status were included in the study. The Postconcussion Symptom Inventory (PCSI) item assessing headache was used as the outcome variable. Logistic regression was used to examine the association between the risk of developing headache and sociodemographic and health-related factors. Results Slightly less than half of the participants reported the presence of headache (TBI sample: 46%; matched controls: 44%). Compared with matched controls, the odds of headache in the TBI sample were not significantly different (OR = 1.09, 95% CI 0.85 to 1.4, p = 0.49). The association between PCSI symptoms was generally stronger in adolescents than in children and in the matched controls than in the TBI sample. In the TBI sample, the probability of reporting headache increased with age. Conclusions The results of this study suggest that the prevalence of headache in the post-acute phase of pediatric TBI is not significantly different from that in the matched non-TBI population, indicating good recovery from injury. However, due to its high prevalence, follow-up screening for this common TBI symptom, especially in adolescents, may be helpful to prevent further chronification. Trial registration The study is retrospectively registered in German Clinical Trials Register and in International Clinical Trials Registry Platform (ID DRKS00032854).